Strategic Optimization of School Administrative Management Using Google Workspace for Education - Agnes Deta Waluyaningtyas; Jumintono; Didi Supriadi; Hazel Dorothy C. Vilan (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2025)
This study aims to explore the implementation of Google Workspace for Education in school administration and to formulate effective strategies for optimizing administrative processes at a State Junior High School in Yogyakarta. Employing a qualitative research approach, data were collected through interviews, observations, document analysis, and questionnaires. The study investigated how Google Workspace tools are integrated into administrative tasks and identified internal and external factors influencing its adoption using a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. Findings reveal that Google Workspace for Education is effectively utilized in managing curriculum and student administration, particularly through online collaboration facilitated by Google Drive, Google Docs, Google Spreadsheets, Google Forms, and Google Sites. The school has established a development team and conducts regular evaluations to ensure the effectiveness of administrative functions. Based on SWOT analysis, the study recommends a progressive strategy that leverages the school's internal strengths to capitalize on external opportunities, thereby enhancing administrative efficiency. This strategic approach underscores the role of digital tools in promoting innovation and improving school governance.